Tensions and challenges between community health agents and their teams - Carvalho Romagnoli, Roberta; Lurdes Pires Samudio, Jania (Revista Pesquisas e Práticas Psicossociais, 2017)
Primary Health Care (PHC) in Brazil consists of Family Health Strategy (FHS) teams, composed of medical professionals, nurses, nursing technicians, dentists, dental technicians and Community Health Agents (CHA). As a gateway to the healthcare model, the FHS is the first contact of users with the health system. Therefore, because of its proximity to the community and families, the CHA becomes the first professional to identify and accept cases. This article proposes to analyze the relationship between the CHA and the teams from a schizoanalytic perspective. The results point to an overload of work on the CHA and power relations based on knowledge leading to its devaluation by the team. We conclude that, despite these tensions, the work of the CHA is essential for the consolidation of Primary Health Care in Brazil. Keywords: Primary Health Care. Community Health Agent. Power relationships. Biopower.